The discretion of the EU Member States in shaping the non-conviction based confiscation regime in the light of CJEU and ECHR case law - Wycichowski-Kuchta, Gniewomir (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
The research presented in the article aims to assess the scope of the normative freedom of EU Member States when implementing non-conviction based confiscation. This study was based on the case law of the Court of Justice of the European Union (CJEU) and the European Court of Human Rights (ECHR). The study shows that despite the broad discretion of the Member States resulting from the position of the CJEU, domestic regulation of this type of confiscation falls outside the scope of EU law; the extensive jurisprudence of the ECHR sets quite precise boundaries concerning the concept of confiscation without prior conviction. Thus, it limits the discretion of Member States in this regard, providing both safeguards for individuals and guidelines for national legislators that intend to develop non-conviction based confiscation regimes in their domestic legal system.